2021
DOI: 10.30519/ahtr.799716
|View full text |Cite
|
Sign up to set email alerts
|

The Mediating Role of Real-Time Information Between Location-Based User-Generated Content and Tourist Gift Purchase Intention

Abstract: The global use of Web 2.0 applications has generated enormous volumes of user content. Drawing on cognitive load theory, this study examines unexplored factors that influence gift purchase intention of tourists. The authors identify localization and realtime information for shaping tourists' gift purchase intention, which is facilitated by reduced cognitive overload. Analyzes of the study relies on a sample of 273 foreign tourists in Malaysia. A cross-sectional quantitative study is conducted using partial lea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 131 publications
1
8
0
Order By: Relevance
“…The finding revealed that BI partially mediates the relationship between CO, COM, IFC, and CS. These findings are similar to previous studies, which asserted that CDMO maintains a positive BI (Khan, Khan et al, 2021a, 2021b), which leads to a high degree of CS (Anwar et al, 2019; Eklof et al, 2020; Khan & Ghouri, 2018; Khan, Khan et al, 2021a, 2021b), provides favorable market position and ultimately improve business performance (Rybaczewska et al, 2020). The potential clarification for these findings is that once all three dimensions of MO were effectively implemented by ethnic food businesses, it helped to create a BI in the minds of customers, which led to CS.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…The finding revealed that BI partially mediates the relationship between CO, COM, IFC, and CS. These findings are similar to previous studies, which asserted that CDMO maintains a positive BI (Khan, Khan et al, 2021a, 2021b), which leads to a high degree of CS (Anwar et al, 2019; Eklof et al, 2020; Khan & Ghouri, 2018; Khan, Khan et al, 2021a, 2021b), provides favorable market position and ultimately improve business performance (Rybaczewska et al, 2020). The potential clarification for these findings is that once all three dimensions of MO were effectively implemented by ethnic food businesses, it helped to create a BI in the minds of customers, which led to CS.…”
Section: Discussionsupporting
confidence: 91%
“…PLS is suitable for theory building and testing studies (Hulland, 1999;Khan, Khan et al, 2021a, 2021b. PLS-SEM enables simultaneous automated corrections for measurement errors while handling independent and dependent latent variables (Hair et al, 2014;Khan, Khan et al, 2021a, 2021b. PLS path modeling is used in this research to analyze the reliability (rho), Cronbach's alpha (a), convergent validity (AVE), and discriminant validity (HTMT) (Hair et al, 2019;.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations